DEVELOPMENT OF MOODLE-BASED LEARNING MANAGEMENT SYSTEM (LMS) ON DISCOVERY LEARNING MODEL - Ahmad, Dina Amelia; Side, Sumiati; Jusniar, Jusniar (JCER (Journal of Chemistry Education Research), 2024)
This development research aims to produce valid, practical, and effective LMS products. The development of this LMS refers to the ADDIE development model. The research was conducted at SMAN 22 Makassar in August-December 2022. There were four subjects in this study, namely media experts and material experts as validity test subjects, chemistry subject teachers and 10 students of XII MIPA 2 students as subjects for small group test and participants students in class XI MIPA 2 totaled 34 students as practical and effectiveness test subjects. The instruments used for validity were validation sheets by media experts and material experts, practicality, namely LMS learning implementation observation sheets, teacher and student response questionnaires, and effectiveness, namely learning achievement tests. Based on data analysis, it was concluded that the developed Moodle-Based LMS was valid, practical, and effective for use in learning.